2021
DOI: 10.1186/s13018-021-02514-2
|View full text |Cite
|
Sign up to set email alerts
|

How much improvement can satisfy patients? Exploring patients’ satisfaction 3 years after total knee arthroplasty

Abstract: Background Despite the innovations in total knee arthroplasty (TKA), there is still a subset of patients who do not acquire significant relief or expected satisfaction after primary TKA. However, this subgroup of patients still gains improvements more or less in terms of objective or quantified assessments after the procedure. The purpose of our study is to explore the factors that correlate with patients’ satisfaction and identify minimal clinically important difference (MCID) and minimum impo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Therefore, the study hypothesis was rejected. The minimal clinically important difference (MCID) is an important issue and some scoring systems have been evaluated for patient satisfaction [12]. In the current study, the FCs were found to be more externally rotated and the PCO ratio was higher in the GB group than in the MR group in the TKAs.…”
Section: Discussionmentioning
confidence: 60%
“…Therefore, the study hypothesis was rejected. The minimal clinically important difference (MCID) is an important issue and some scoring systems have been evaluated for patient satisfaction [12]. In the current study, the FCs were found to be more externally rotated and the PCO ratio was higher in the GB group than in the MR group in the TKAs.…”
Section: Discussionmentioning
confidence: 60%
“…Ranawat’s classification was used to assess valgus deformity and Thienpont’s classification was used to evaluate the varus deformity of the knee joint [ 15 , 16 ]. The minimum clinically important difference (MCID) used for the HSS was 5.41 [ 17 ].…”
Section: Methodsmentioning
confidence: 99%
“…For each measurement, the result was recorded in the outpatient medical record. Patients were considered to have attained the minimal clinically important difference (MCID) when their improvement in scores were greater than 5.4 for HSS, 15) 6.1 for KSS function, 16) and 17.0 for WOMAC. 17 18) The American Society of Anesthesiologists physical status classification system was used to assess the fitness of patients by anesthesiologists in the hospital for the prediction of anesthetic and surgical risks prior to the procedure.…”
Section: Methodsmentioning
confidence: 99%